Electrochemical detection of type 2 diabetes mellitus-related SNP via DNA-mediated growth of silver nanoparticles on single walled carbon nanotubes. Issue 86 (14th September 2015) - Tao, Jia; Zhao, Peng; Zheng, Jing; Wu, Cuichen; Shi, Muling; Li, Jishan; Li, Yinhui; Yang, Ronghua
Abstract : In this communication, we proposed an electrochemical sensing strategy for T2DM-related SNP detection via DNA-mediated AgNP growth on a SWCNT-modified electrode. Abstract : Herein, we proposed a new electrochemical sensing strategy for T2DM-related SNP detection via DNA-mediated growth of AgNPs on a SWCNT-modified electrode. Coupled with RNase HII enzyme assisted amplification, this approach could realize T2DM-related SNP assay and be applied in crude extracts of carcinoma pancreatic β-cell lines.